Dissection of the role of p62/Sqstm1 in activation of Nrf2 during xenophagy. Issue 5 (1st February 2014) - Ishimura, Ryosuke; Tanaka, Keiji; Komatsu, Masaaki
Abstract : Upon infection of a cell by Salmonella, p62/Sqstm1 assembles on the microbes; simultaneously, p62/Sqstm1 is phosphorylated at Ser351, leading to inactivation of Keap1, which is responsible for degrading Nrf2. Thus, cytoprotective Nrf2 targets are induced at the same time that autophagosomes entrap the microbes (xenophagy). However, the detailed role of p62/Sqstm1 during xenophagy has remained unclear. Here we show that translocation of p62/Sqstm1 to invasive Salmonella precedes Ser351 phosphorylation. Furthermore, in addition to Ser351 phosphorylation, oligomerization of p62/Sqstm1 is also required for localization of Keap1 onto microbes, which is followed by Nrf2 activation. Our data reveal the sequential dynamics of p62/Sqstm1 in response to bacterial infection. Abstract : Ubiquitin‐chain binding of p62 is required for its translocation to invasive Salmonella . Localization of p62 on invasive Salmonella precedes its phosphorylation of Ser351. Oligomerization of p62 is required for phosphorylation of Ser351. p62 is essential for Nrf2 activation during xenophagy but not for xenophagy itself.